Interpretation on the Guidelines for the Diagnosis and Treatment of Chronic Thromboembolic Pulmonary Hypertension(2024 edition) - YANG Furong; XIE Wanmu (Xiehe Yixue Zazhi)
Chronic thromboembolic pulmonary hypertension (CTEPH), a severe long-term complication of acute pulmonary thromboembolism, is characterized by high mortality and disability rates.The Guidelines for the Diagnosis and Treatment of Chronic Thromboembolic Pulmonary Hypertension(2024 edition) represents the first comprehensive systematic evaluation of evidence-based medical evidence on CTEPH published domestically and internationally in recent years, formulating recommendations tailored to clinical practice in China to standardize the clinical diagnosis and management of CTEPH. This article provides an interpretative analysis focusing on early recognition of CTEPH, the diagnostic value of various imaging modalities, and the selection of therapeutic strategies, with the aim of providing clinical guidance and support.